Skipjack tuna fishing season and its relationship with oceanographic conditions in Palabuhan Ratu Waters, West Java - Tri Wiji Nurani,; Wahyuningrum, Prihatin Ika; Iqbal, Muhammad; Nurani Khoerunnisa,; Pratama, Gilar Budi; Elvanri Anggi Widianti,; Kurniawan, Muhammad Fikri (Penerbit Universiti Kebangsaan Malaysia, 2022)
Skipjack tuna (Katsuwonus pelamis) is the main catch species in Indonesian Palabuhanratu waters. The dynamics of skipjack fishing areas are influenced by oceanographic parameters such as sea surface temperature and chlorophyll-a concentration. This study aims to predict the skipjack fishing season, to analyze the dynamics of oceanographic conditions, especially the distribution of both sea surface temperature and chlorophyll-a, and to determine the relationship between skipjack fishing season and the dynamic distribution of sea surface temperature and chlorophyll-a concentration in the Palabuhanratu waters, West Java. Catch per unit effort analysis was used to determine the fishing season index. At the same time, the dynamics of sea surface temperature and distribution of chlorophyll-a were analyzed from monthly MODIS image data from 2015 to 2019. This study showed that skipjack fishing season in Palabuhanratu waters was from July to November. Monthly sea surface temperatures range from 26-30 ºC with an average value of 29 ºC. The concentration of the chlorophyll-a was 0.09 to 0.51 mg/ m3 (average of 0.23 mg/m3). There was a negative relationship between sea surface temperature and skipjack tuna production, while a positive relationship with the chlorophyll-a concentrations.